Coordination Polymer: Synthesis, Spectral Characterization and Thermal Behaviour of Starch-Urea Based Biodegradable Polymer and Its Polymer Metal Complexes - Ashraf Malik; Shadma Parveen; Tansir Ahamad; Saad M. Alshehri; Prabal Kumar Singh; Nahid Nishat (Bioinorganic Chemistry and Applications)
A starch-urea-based biodegradable coordination polymer modified by transition metal Mn(II), Co(II), Ni(II), Cu(II), and Zn(II) was prepared by polycondensation of starch and urea. All the synthesized polymeric compounds were characterized by Fourier transform-infrared spectroscopy (FT-IR), H-NMR spectroscopy, C-NMR spectroscopy, UV-visible spectra, magnetic moment measurements, differential scanning calorimeter (DSC), and thermogravimetric analysis (TGA). The results of electronic spectra and magnetic moment measurements indicate that Mn(II), Co(II), and Ni(II) complexes show octahedral geometry, while Cu(II) and Zn(II) complexes show square planar and tetrahedral geometry, respectively. The thermogravimetric analysis revealed that all the polymeric metal complexes are more thermally stable than the parental ligand. In addition, biodegradable studies of all the polymeric compounds were also carried out through ASTM standards of biodegradable polymers by CO2 evolution method.